Model Immigrants and Undesirable Aliens - Christina Gerken (University of Minnesota Press, 2013)
Congressional debates from the mid- ï›œï™ï™ï˜¹s suggest that the U.S. immigration system had reached a point of crisis. According to the dominant political rhetoric, immigration laws failed to protect U.S. citizens from an overwhelming infl ux of undesirable immigrants who, unlike previous generations of newcomers, were reluctant to blend in with the majority culture and contribute to the economy. Politicians frequently referred to this seemingly unprecedented crisis in their calls for immediate and drastic immigration reform measures. For example, when Senator Richard Shelby (R- AL) spoke in favor of the Immigration Control and Financial Responsibility Act of ï›œï™ï™ï˜¾ (S. ï›œï˜¾ï˜¾ï˜¼), he argued that immigrants â€œput a crippling strain on the American education systemâ€ and placed a burden on taxpayers by committing crimes, displacing U.S. workers, and using public welfare services, including emergency medical care (United States Congress, Senate, April ï˜ºï˜½, ï›œï™ï™ï˜¾). In a carefully worded remark (interspersed with proclamations that he was neither anti- immigrant nor racist), Senator Shelby also contended that current immigrants were less desirable because they were culturally and ethnically diff erent from â€œour domestic populationâ€ and were thus slower to assimilate, especially in a society where â€œmulticulturalism is favored over the â€˜melting potâ€™ conceptâ€ (United States Congress, Senate, April ï˜ºï˜½, ï›œï™ï™ï˜¾). Over time, many have pushed to reduce overall admissions and reform admission criteria because of the changing cultural and ethnic heritage of immigrants; this idea is far from original. In the late nineteenth century, the New York Times expressed a similar concern over the increasing number of Eastern and Southeastern European immigrants. In an article from ï›œï™€ï™ï˜º, the New York Times argued that past generations of Northwestern European immigrants â€œwere readily assimilated and made good citizens.â€ However, with a new wave of immigrants, â€œnew and unclean fountains burst in the east and southeast, the swelling streams pouring in a people wholly diff erent in race, character, traditions, purpose and social lifeâ€ (â€œImmigration Problems,â€ Th e New York Times, November ï˜ºï˜¾, ï›œï™€ï™ï˜º). In the ï›œï™ï˜ºï˜¹s, in an eff ort to justify the passage of a national quota law, politicians warned of the potentially disastrous eff ects of turning America into a â€œconglomeration of racial groups each advocating a diff erent set of ideas and ideals according to their bringing upâ€ (James Davis, â€œOne Hundred Years of Immigration,â€ Th e New York Times, February ï›œï˜¿, ï›œï™ï˜ºï˜¼). But despite obvious similarities, Senator Shelbyâ€™s comments are also fundamentally diff erent from his predecessorsâ€™ concerns. Not only is Shelby careful to refrain from using openly racist language by focusing on the damaging eff ects of multiculturalism instead of race/ethnicity itself, but he expresses his views on the racial/ethnic makeup of the immigrant population as part of a much larger concern about the economic and social consequences of large- scale immigration. Th is book argues that the immigration reform discourse of the mid- ï›œï™ï™ï˜¹s represents a new way of thinking and talking about immigration. In particular, later chapters discuss the productive tension between Congressâ€™s pronounced eff ort to discuss immigration reform as an economic issue and the underlying anxieties about immigrantsâ€™ race, class, gender, and sexuality. As part of a larger neoliberal reform process in the mid- ï›œï™ï™ï˜¹s, politicians linked proposals to develop a nationwide system to identify â€œlegalâ€ and â€œillegalâ€ immigrants with welfare legislation, measures that were supposed to prevent/fi ght terrorism, encourage economic security, and provisions concerning marriage/family structure.ï›œ Within this larger reform discourse, immigrants were repeatedly cited as one of the principal causes of the nationâ€™s high poverty rate, the increasing costs of social welfare, a decline in traditional values, and the need to pass ever more invasive and restrictive immigration and welfare reform measures.